De Novo Sirolimus and Reduced‐Dose Tacrolimus Versus Standard‐Dose Tacrolimus After Liver Transplantation: The 2000–2003 Phase II Prospective Randomized Trial - Asrani, S. K.; Wiesner, R. H.; Trotter, J. F.; Klintmalm, G.; Katz, E.; Maller, E.; Roberts, J.; Kneteman, N.; Teperman, L.; Fung, J. J.; Millis, J. M. (American journal of transplantation, 2014)
We studied whether the use of sirolimus with reduced‐dose tacrolimus, as compared to standard‐dose tacrolimus, after liver transplantation is safe, tolerated and efficacious. In an international multicenter, open‐label, active‐controlled randomized trial (2000–2003), adult primary liver transplant recipients (n = 222) were randomly assigned immediately after transplantation to conventional‐dose tacrolimus (trough: 7–15 ng/mL) or sirolimus (loading dose: 15 mg, initial dose: 5 mg titrated to a trough of 4–11 ng/mL) and reduced‐dose tacrolimus (trough: 3–7 ng/mL). The study was terminated after 21 months due to imbalance in adverse events. The 24‐month cumulative incidence of graft loss (26.4% vs. 12.5%, p = 0.009) and patient death (20% vs. 8%, p = 0.010) was higher in subjects receiving sirolimus. A numerically higher rate of hepatic artery thrombosis/portal vein thrombosis was observed in the sirolimus arm (8% vs. 3%, p = 0.065). The incidence of sepsis was higher in the sirolimus arm (20.4% vs. 7.2%, p = 0.006). Rates of acute cellular rejection were similar between the two groups. Early use of sirolimus using a loading dose followed by maintenance doses and reduced‐dose tacrolimus in de novo liver transplant recipients is associated with higher rates of graft loss, death and sepsis when compared to the use of conventional‐dose tacrolimus alone. This study reports the results of the international, multicenter, controlled randomized trial of adult primary liver transplant recipients receiving de novo sirolimus and reduced dose tacrolimus or conventional dose tacrolimus, which formed the basis of a black box warning for use of sirolimus immediately after liver transplantation. See editorial by Levitsky and Feng on page 249.